HEALTH ADVERTISING ON INSTAGRAM: IS IT EFFECTIVE WHILE FOLLOWING ETHICAL GUIDELINES? - Anky Angga Alhudha; Winny Setyonugroho; Firman Pribadi (Universitas Airlangga, 2024)
Background: Given the popularity of digital marketing in business today, every hospital can start utilizing it by establishing a social media account. Instagram is a social media platform that focuses on photographs. The AISAS (Attention, Interest, Search, Action, and Share) model can be used to assess the efficacy of marketing communications. Regardless, there are issues regarding legal and ethical issues. Therefore, a question emerges: How can health advertisements be effective while following ethical guidelines? Aims: The purpose of this research is to analyze the content of healthcare advertisements on Instagram Methods: This study uses the quantitative descriptive content analysis method. The samples are Instagram advertisements for health services. Search them using the hashtags (#) #dokterjogja, #klinikjogja, #klinikyogyakarta, and #rumahsakitjogja. Using convenience sampling, the researcher randomly scrolls and stops on Instagram. The data were assessed by two coders using a checklist to ensure objectivity. The checklist contains three indicators, in this case, the AIA (Attention, Interest, Action) indicator, and the other indicators were obtained from the Regulation of the Minister of Health of the Republic of Indonesia (PERMENKES) number 1787 of 2010 Results: The highest score of the AIA (Attention, Interest, Action) indicator is 12, and there are a total of 34 advertisements (coder 1), and 84 advertisements (coder 2) violate The Regulation of the Minister of Health (PERMENKES) No.1787/2010 Conclusion: This study finds that effective advertising is almost certain to violate the regulation. An educational health information advertisement that introduces the services provided is a good way to promote healthcare providers while remaining ethical. Keywords: advertising, AISAS, ethics, health, social media